The analysis and protection of systems containing series compensated power lines - Sanderson, J.V.H. (1973)
Series capacitors are used extensively to reduce the power transfer impedance of long transmission lines. During times of high current, the capacitors are protected from the build-up of high voltages by spark gaps with which they are connected in parallel. This non-linearity affects the behaviour of the system as a whole. Firstly, this thesis is concerned with studying the system behaviour.